Numerical modeling of radiated sound for impact pile driving in offshore environments - Wilkes, D.; Gourlay, T.; Gavrilov, Alexander (Institute of Electrical and Electronics Engineers, 2016)
In this paper, a coupled near-to-far-field numerical model for predicting the acoustic emissions from impact pile driving in offshore environments is presented. The near-field region of the pile is modeled via an axisymmetric finite element method (FEM) model which is solved in the frequency domain. The calculated radiated field at a chosen radial distance in the FEM model is then expanded into a series of local normal modes (NMs) which are propagated into the far field, to predict the piling sound characteristics, such as the peak pressure and sound exposure levels, at large ranges. Numerical examples are presented for the same pile configuration adopted for the COMPILE 2014 benchmark workshop on predicting offshore pile-driving noise, and these results are compared in both the near and far fields to those of several other research groups who presented results at the workshop. Results from the present FEM-NM near-to-far-field model are shown to be generally in good agreement with those results from the other research groups. In the near field, similar signal waveforms are predicted by the various models which employ the same pile wall boundary conditions. In the far field, the selected models showed a variation of ±1 dB at 1.5 km, and ±4 dB at 50 km for the predicted peak pressure levels, and a variation of ±1.5 dB over the 50-km range for the predicted sound exposure levels.